2014
DOI: 10.1158/1535-7163.mct-14-0345
|View full text |Cite
|
Sign up to set email alerts
|

Redirected T-Cell Killing of Solid Cancers Targeted with an Anti-CD3/Trop-2–Bispecific Antibody Is Enhanced in Combination with Interferon-α

Abstract: Trop-2 has limited presence on normal tissues but is highly expressed in diverse epithelial cancers. (E1)-3s is a T-cell-redirecting trivalent bispecific antibody (bsAb), comprising an anti-CD3 scFv covalently linked to a stabilized dimer of a Trop-2-targeting Fab using Dock-and-Lock. We show for the first time that bsAbmediated bidirectional trogocytosis occurs between target and T cells and involves immunologic synapses. We studied the effects of interferon-a (INFa) on (E1)-3s-mediated T-cell killing of huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…Because these processes are inhibited by VHH 5E7, it is likely that VHH 5E7 inhibits the formation of immunological synapses between Vg9Vd2 T cells and target cells. This is supported by our observation that VHH 5E7, but not a nonspecific control VHH, dose-dependently inhibited trogocytosis, an active, rapid, and polarized bidirectional exchange of membrane patches in the immunological synapse that forms between immune effector and target cells (50)(51)(52)(53), that is, between Vg9Vd2 T cells and phosphoantigen-expressing target cells (Supplemental Fig. 1).…”
Section: Identification and Characterization Of Neutralizing Vg9vd2 Tsupporting
confidence: 70%
“…Because these processes are inhibited by VHH 5E7, it is likely that VHH 5E7 inhibits the formation of immunological synapses between Vg9Vd2 T cells and target cells. This is supported by our observation that VHH 5E7, but not a nonspecific control VHH, dose-dependently inhibited trogocytosis, an active, rapid, and polarized bidirectional exchange of membrane patches in the immunological synapse that forms between immune effector and target cells (50)(51)(52)(53), that is, between Vg9Vd2 T cells and phosphoantigen-expressing target cells (Supplemental Fig. 1).…”
Section: Identification and Characterization Of Neutralizing Vg9vd2 Tsupporting
confidence: 70%
“…21). We have also demonstrated in a follow-on study with (E1)-3s, a representative (X)-3s with specificity for Trop-2-expressing epithelial cancer cells, that the addition of interferon-a (IFN-a) further enhanced the potency of redirected T cells in vitro without a significant increase in cytokine production, and that the combination of (E1)-3s with peginterferon alfa-2a more effectively delayed the growth of Trop-2-expressing NCI-N87 human gastric cancer xenografts in vivo than single treatments with either (E1)-3s or peginterferon alfa-2a (28). In the current study, we provide evidence that the combination of a novel PD-1-blocking antibody (cPD-1) with (E1)-3s or the CEACAM5targeting (14)-3s could potentiate the antitumor activity of redirected T cells against target human cancer cells grown in vitro as monolayer cultures or three-dimensional (3D) multicellular tumor spheroids (MCTS; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated the benefit of IFN-α as an adjuvant to chemotherapy and radiation treatments following the resection of malignant tumors, including cancers of the digestive system [10-13]. Cell culture and animal studies have also shown that treatments that included IFN-α inhibited the proliferation and metastasis of hepatocellular carcinoma [14], gastric cancer, and pancreatic cancer cells [15]. However, recent studies have shown that IFN signaling is also involved in immunosuppression [16].…”
Section: Introductionmentioning
confidence: 99%